2016
DOI: 10.1002/pssa.201600472
|View full text |Cite
|
Sign up to set email alerts
|

Zinc nitride as a potential high-mobility transparent conductor

Abstract: Polycrystalline and epitaxial zinc nitride (Zn3N2) films were grown by a reactive rf‐magnetron sputtering technique. Phase‐pure films were grown but XPS results indicated that a small amount of oxygen exists within all Zn3N2–xOx films. We prove experimentally that substitutional O on the N site (normalOnormalN•) can be treated as an electron donor. The electrical and optical properties can be tuned by tuning the x values. High mobilities were achieved in both polycrystalline and epitaxial Zn3N2 films. In‐depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…First principle studies predicted m c * values to be as small as ~0.1 m 0 in both ordered- and disordered ZnSnN 2 4 , 9 , 25 , 26 . The predicted m c * values are comparable to those in other III–V and Zn-based nitride semiconductors including InN (0.055 m 0 ) 27 , GaN (0.2 m 0 ) 28 , GaAs (0.083 m 0 ) 29 , and Zn 3 N 2 (0.08 m 0 ) 30 . Although small m c * values generally leads to high electron mobility ( μ) , μ values in the ZnSnN 2 epilayers have been reported to be less than or equal to 10 cm 2 V −1 s −1 9 , 10 .…”
Section: Resultssupporting
confidence: 70%
“…First principle studies predicted m c * values to be as small as ~0.1 m 0 in both ordered- and disordered ZnSnN 2 4 , 9 , 25 , 26 . The predicted m c * values are comparable to those in other III–V and Zn-based nitride semiconductors including InN (0.055 m 0 ) 27 , GaN (0.2 m 0 ) 28 , GaAs (0.083 m 0 ) 29 , and Zn 3 N 2 (0.08 m 0 ) 30 . Although small m c * values generally leads to high electron mobility ( μ) , μ values in the ZnSnN 2 epilayers have been reported to be less than or equal to 10 cm 2 V −1 s −1 9 , 10 .…”
Section: Resultssupporting
confidence: 70%
“…Exceeding the degradation temperature of amides within ammonothermal syntheses could afford crystal growth of other promising nitride materials as well. For instance, Zn 3 N 2 represents an intriguing narrow‐gap semiconductor material featuring small carrier effective masses and high carrier mobility . Supposable intermediates in ammonobasic and ‐acidic systems were already reported, while its ammonothermal synthesis was assumed to require considerably higher process temperatures .…”
Section: Future Challenges and Perspectivesmentioning
confidence: 95%
“…For instance, Zn 3 N 2 represents an intriguing narrow-gap semiconductor material featuring small carriere ffective masses and high carrier mobility. [109,168] Supposable intermediates in ammonobasic and -acidic systemsw ere already reported, while its ammonothermal synthesis was assumed to requirec onsiderably higherp rocess temperatures. [169,170] Moreover,n ew elementc ombinations and mineralizer systems, along with an extension of parameter limits, could promotet he discovery of novel multinaryn itride materials as our recent studies already demonstrated.…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…sputt.) are also shown by points [14,16,18,70]. A horizontal arrow shows a range of experimentally reported electron carrier concentration, and a vertical one the range of the corresponding optical gaps.…”
Section: B Carrier-induced Optical-gap Variationmentioning
confidence: 97%